Analysis of Culinary Digital Literacy and Promotion Strategies in Makassar City Through Instagram Social Media: A Qualitative Study on Instagram Account - Andi Caezar To Tadampali; Ika Wisudawaty; Sri Hutami Adiningsih S (Universitas Sulawesi Barat, 2026)
This study explores how digital literacy shapes social media–based culinary promotion strategies on Instagram. Using a qualitative research approach, the study focuses on the @mksmakan account as a case study to gain an in-depth understanding of promotional practices, content strategies, and audience engagement mechanisms. Data were collected through in-depth interviews, observation of Instagram content, and documentation, and were analyzed using thematic analysis. The findings reveal that effective culinary promotion on Instagram is closely related to the account manager’s digital literacy, particularly in content creation, audience interaction, and data-driven decision-making. Strategies such as content collaboration, giveaways, and the prioritization of Instagram Reels emerge as key practices that enhance engagement and visibility. Rather than establishing causal relationships, this study illustrates how digital literacy enables adaptive promotional strategies in response to platform algorithms and audience behavior. From a theoretical perspective, this study offers two main contributions. First, it extends Social Media Marketing Theory by demonstrating how engagement-oriented strategies are enacted in a local culinary promotion context. Second, it enriches Digital Literacy Theory by highlighting the role of analytical and strategic competencies in everyday social media management. The findings provide practical insights for culinary business actors, content creators, and policymakers seeking to strengthen digital promotion practices within the creative economy sector